2016
DOI: 10.1111/mpp.12458
|View full text |Cite
|
Sign up to set email alerts
|

Apyrase inhibitors enhance the ability of diverse fungicides to inhibit the growth of different plant‐pathogenic fungi

Abstract: A previous study has demonstrated that the treatment of Arabidopsis plants with chemical inhibitors of apyrase enzymes increases their sensitivity to herbicides. In this study, we found that the addition of the same or related apyrase inhibitors could potentiate the ability of different fungicides to inhibit the growth of five different pathogenic fungi in plate growth assays. The growth of all five fungi was partially inhibited by three commonly used fungicides: copper octanoate, myclobutanil and propiconazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
(82 reference statements)
1
1
0
Order By: Relevance
“…Consistent with previous reports showing that APY inhibitors enhanced the potency of herbicides [ 36 ], Tripathy et al [ 96 ] showed that several of these highly specific inhibitors also enhanced the potency of three different fungicides, copper octanoate, myclobutanil and propiconazole to suppress the growth of five different pathogenic fungi. The pathogen most sensitive to the increased fungicidal potency resulting from the inhibitor additions was Sclerotinia .…”
Section: Potential Value Of Apyrase Inhibitorssupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with previous reports showing that APY inhibitors enhanced the potency of herbicides [ 36 ], Tripathy et al [ 96 ] showed that several of these highly specific inhibitors also enhanced the potency of three different fungicides, copper octanoate, myclobutanil and propiconazole to suppress the growth of five different pathogenic fungi. The pathogen most sensitive to the increased fungicidal potency resulting from the inhibitor additions was Sclerotinia .…”
Section: Potential Value Of Apyrase Inhibitorssupporting
confidence: 89%
“…More recently, Tripathy et al [ 96 ] tested whether some of the APY inhibitors selected by Windsor et al [ 36 ] could be used to enhance the potency of fungicides. A strong rationale for the potential benefit of this study was that fungi constitute the largest number of plant pathogens, causing a wide range of plant diseases, and in current agricultural practices, many chemical fungicides have been used in high doses and frequent intervals to prevent crop losses [ 97 ].…”
Section: Potential Value Of Apyrase Inhibitorsmentioning
confidence: 99%